Análise da mobilidade urbana por transporte sustentável nas cidades médias brasileiras - Silva, Wellington Nascimento (2017)
The objective of this thesis was to explain the urban mobility by means of sustainable transport in the medium Brazilian cities basing on an exploratory econometric model formed by demographic, urban, income and transport system (DURT) variables. The explanation and model could be useful for public managers because it can possible for them to develop public policies to reduce or eliminate the negative externalities of the urban mobility. The diversity of Brazilian cities with different characteristics made it difficult to create a unique model that could be applied to all of them but there are cities with sufficient similarities to create a specific model for their characteristics. The variables of the model were the economically active population, the per capita income, the urban density, motorization rate for collective transport, the motorization rate for private transport, the motorization rate for motorcycles and the urban form, that represented a set of variables compoused by the urban design and location of cities in metropolitan or inland states. The analyzes indicated that the motorization rate for motorcycles and the design have the greatest potential to reduce travel by sustainable transport while the motorization rate for collective transport and percapita income have the greatest potential to create travels by sustainable transport.